Trehalose coated nanocellulose to inhibit the infections by S. aureus. Issue 11 (2nd February 2022) - Li, Yimeng; Milewska, Małgorzata; Khine, Yee Yee; Ariotti, Nicholas; Stenzel, Martina H.
Abstract : Preventing bacterial infection by using anti-adhesive trehalose polymer is one alternative to antibiotic treatment. Abstract : Preventing bacterial infection by using anti-adhesive compounds is one alternative to antibiotic treatment. Trehalose based polymers can serve as an anti-adhesive agent that are selective to bacteria as trehalose is widely used by bacteria, but there is no mechanism in mammals that processed this disaccharide. To generate an efficient trehalose-based anti-adhesive, we modified TEMPO-oxidized cellulose nanofibers (CNFs) using aldehyde-terminated trehalose polymer poly(6- O -acryloyl-trehalose) (PTre), which were prepared by RAFT polymerization, via Passerini reactions. The grafting efficiency was found to be around 35% w/w resulting in CNF-PTre with good dispersibility in water. Moreover, a control based on poly(2-hydroxy ethyl) acrylate PHEA was prepared. Both functional CNFs were non-toxic against to RAW 264.7 at concentration up to 500 μg mL −1 . The anti-adhesion effects of both functional CNFs were evaluated at concertation of 100 and 200 μg mL −1, using the S. aureus -HUVECs infection system. The treatments of CNF-PTre at 200 μg mL −1 led to a significant infection reduction of 80% while CNF-PHEA at 200 μg mL −1 decreased infections by 54% suggesting the CNF can act as anti-adhesive agent by simple steric stabilization. To generate a nanoparticle that is capable of inhibiting adhesion while as reducing bacteria growth, ciprofloxacin was loaded onto CNF-PTre by ionic interaction. The resulting CNF-PTre-Cip showed an antibacterial activity against S. aureus and P. aeruginosa at a same level of free ciprofloxacin, indicating the successful release of loaded ciprofloxacin. Analysis of the rate of release at pH 7.4 and pH 5.5 showed a faster release at pH 7.4 and the drug was released in a burst-like fashion in only a few hours.